PENERAPAN MODEL PEMBELAJARAN PACE DALAM MENINGKATKAN KEMAMPUAN MENGGAMBAR MAHASISWA PADA KONSEP VEKTOR - Nur Aida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Vocational education is an educational program that aims to prepare personnel who can establish expertise and skills in their field. For example, students majoring in civil engineering are expected to master skills in drawing designs and measuring distances and directions. In basic courses, student will take physics and mathematics courses, where one of the concepts studied is measuring the size of angles and the resultant of several vectors. The purpose of this study is to describe the application of the PACE learning model to improve the drawing skills of students majoring in civil engineering. The type of research used is descriptive research. The research subject first semester students of the Civil Engineering Department for the 2021/2022 academic year, totaling 62 people. Data analysis using SPSS software with descriptive test. After students have learned, most of the 45 students (75%) can use arcs well, and put the initial position of a vector’s distance, and continue with the second, third, anda resultant vectors with the correct direction and angle positions. The application of the PACE learning model has a significant effect on students’ drawing skills in vector material. Students not only acquire cognitive knowledge, but have affective and spicomotor skills in terms of drawing and using rules and arcs.